La atención al cliente y su impacto en las ventas de la "Importadora Adrián Imceal Cia Ltda" del cantón la maná, 2021. - Espinoza Valero, Marcia Mery (2022)
Customer service in the business sector is one of the most relevant components in the sales process of commercial companies, which allows customers to purchase the products offered and, in this way, maintain and improve sales volume, being this a transcendental factor that the positioning market establishes. For the reasons already stated, an investigation was developed to analyze the incidence of customer service and its impact on the sales volume of the Importadora Adrián located in La Maná. For the development of the investigative process, it was necessary to apply the deductive method that facilitated the identification of the inherent aspects of customer service and how this factor affects the satisfaction level of customers who purchase in the company. In response to the objectives of the investigation, the information from the primary source, as well as the working hypothesis, was obtained by applying the interview technique to the owner-manager of the company and surveys directed to a total of 273 clients, who contributed with information that, once tabulated and represented in statistical tables and graphs, allowed to identify the results through its respective analysis and interpretation of the collected data. The research results show that 56.8% of those surveyed clients consider the level of satisfaction as excellent for the received attention; 56.4% of customers contemplate the company's sales process as excellent. Similarly, 48.4% of the interviewed clients state that they are totally pleased with the correct registration of the information when they carry out their commercial activities, which provides security and confidence in the personnel who work in the institution.